Treatment and outcome of newly diagnosed multiple myeloma patients > 75 years old: a retrospective analysis. Issue 12 (15th October 2021) - Al Saleh, Abdullah S.; Visram, Alissa; Parmar, Harsh; Muchtar, Eli; Buadi, Francis K.; Dispenzieri, Angela; Warsame, Rahma; Lacy, Martha Q.; Dingli, David; Leung, Nelson; Go, Ronald S.; Gonsalves, Wilson I.; et al.
Abstract: This is a retrospective study of patients with multiple myeloma (MM) who were >75 years old. We identified 394 patients and for non-trial patients ( n  = 350), immunomodulatory drug (IMiD)+dex (32%) was the most commonly used regimen followed by alkylator with steroids or other therapy (21%), alkylator + proteasome inhibitor (PI)+steroid (18%), and IMiD + PI + dex (13%). Overall, achieving ≥ very good partial response was more in patients receiving a triplet compared to other therapies (46% vs. 21%, p  < 0.0001). Also, the median overall survival (OS) was significantly longer in patients who were treated with a triplet (median OS: 50.2 vs. 32.8 months, p  = 0.0006). In a multivariate for OS, receiving a triplet (HR: 0.65, p  = 0.02), not having an R-ISS stage 3 (HR: 0.36, p  = 0.0003), and bone marrow plasma cell percentage <60% (HR: 0.69, p  = 0.03) were predictive. In conclusion, being able to receive triplet therapy was associated with better survival in our MM patients >75 years old.